2021
DOI: 10.1186/s12955-021-01714-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of the French self and proxy versions of the PedsQL™ 4.0 generic health-related quality of life questionnaire for 8–12 year-old children

Abstract: Background The Pediatric Quality of Life Inventory Version 4.0 (PedsQLTM4.0) is a generic health-related quality of life (HRQoL) questionnaire, widely used in pediatric clinical trials but not yet validated in France. We performed the psychometric validation of the self and proxy PedsQLTM4.0 generic questionnaires for French children aged 8–12 years old. Methods This bicentric cross-sectional study included 123 children and their parents with conge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
2
11
1
2
Order By: Relevance
“…Parents tend to acknowledge their children’s receptiveness to their own cues positively. Relatively high ceiling effects for the Social and Cognitive Functioning Scales have been reported previously for infants and children [ 11 , 25 , 26 ]; in the present study, however, they were particularly high. The Social, Cognitive and Emotional Functioning Scales construct the Psychosocial Health Summary in the PedsQL-I.…”
Section: Discussioncontrasting
confidence: 74%
“…Parents tend to acknowledge their children’s receptiveness to their own cues positively. Relatively high ceiling effects for the Social and Cognitive Functioning Scales have been reported previously for infants and children [ 11 , 25 , 26 ]; in the present study, however, they were particularly high. The Social, Cognitive and Emotional Functioning Scales construct the Psychosocial Health Summary in the PedsQL-I.…”
Section: Discussioncontrasting
confidence: 74%
“…Several studies have already evaluated reliability and validity of the transposition of different PedsQL™ Module. [30][31][32][33][34][35][36] Li et al reported the feasibility and the psychometric properties of the Chinese version of the PedsQL™ 3.0 Healthcare Satisfaction Generic Module. [33] Instead, Reinfjell et al recommended the Norwegian version of the Pediatric Quality of Life Inventory™ 4.0 (PedsQL) generic core scales for self-reports and proxy-reports for children in the age groups ranging from 13-15 years.…”
Section: Discussionmentioning
confidence: 99%
“…The PedsQL proxy report form has demonstrated excellent reliability in a paediatric cohort of cancer patients ( a = 0.93) (Varni et al, 2002). In addition, moderate correlations have been observed between the PedsQL and other HR‐QoL questionnaires ( r = 0.4–0.6) in children attending clinical hospital settings (Amedro et al, 2021). The PedsQL has also been found to be effective at discriminating between healthy and ill children (Viecili & Weiss, 2015).…”
Section: Methodsmentioning
confidence: 99%